Relatório de estágio: Programas de treino multicomponente em idosos institucionalizados e da comunidade - Pedro de Meneses Maio (2016)
During the 20th century, we witnessed a progressive ageing of the world population, including the Portuguese (Alves, 2004; Lobo, 2011).This dramatic demographic change leads to more governmental expenses due to a less employed population, with more and more pathologies. Thus, the World Health Organization (WHO) emphasizes that physical activity and physical exercise are fundamental strategies to solve the ageing problem (Cabral & Ferreira, 2013; Silva & Loureiro).The goal of this internship consisted in implementing multicomponent training programs at 3 different groups of elderly people in different contexts and one of resistance trainning. These programs had the duration of 9 months, composed by two weekly sessions of 60 minutes each.In the initial and final phase of the training programs the Senior Fitness Test was applied to each individual in order to evaluate their physical fitness. In order to characterize the sample we used descriptive statistics and to the results of the initial and final phases were compared through the paired T-Test for normal values, whereas for samples with non-normal values the nonparametric test of two related samples, Wilcoxon Test, as conducted (Marôco, 2011). A significance level of 0,05 (p < 0,05) was considered.Our results showed significant differences in all groups, suggesting that a multicomponent and individualized training program positively influences the physical fitness of the elderly adults.